Ein seltenes Epitheton des Gottes Chons-in–Theben-Nfr-ḥtp im Tempel von Dakke - Fernández-Pichel, Abraham Ignacio (Zeitschrift für ägyptische Sprache und Altertumskunde, 2022)
This article presents the typological analogies between two scenes from the temple of Dakka in Lower Nubia representing the Theban triad in its forms of Amun-Re of Abaton, Mut of Isheru and Chonsu m Wȝst Nfr-ḥtp . The unparalleled use in these scenes of an epithet of the god Chonsu in relation to the diospolite region (Seventh nome of Upper Egypt), restored through Richard Lepsius’ handwritten copy of the scene located in the pronaos of the temple, allows us to witness the theological synthesis in Dakka between Theban Chonsu and Neferhotep from Hu. An analysis of the late documentation, mainly from Karnak, allows us to testify to the direct theological connections between these divinities and their various thematic analogies.